Optimum prevention and MX of anaemia in primary care - Jamani, Nurjasmine Aida (2017)
Introduction ⌘  Commonest medical disorder in pregnancy ⌘  1/5 of maternal mortality worldwide ⌘  It is an important contributor to maternal & perinatal morbidity & mortality as a direct or indirect cause